A content analysis of the European food safety Authority's scientific opinion on authorised and rejected appetite-related health claim applications. (March 2023) - Yakubu, Adedamola H.; Platts, Katharine; Sorsby, Anna C.; Clegg, Miriam E.; Paxman, Jenny R.
Graphical abstract: Highlights: 61 appetite-related health claim applications from the EU register were retrieved. Six appetite-related health claims were accepted and 55 rejected by EFSA. Seven main- and 10 sub-categories were revealed through content analysis. The resultant framework offers a means to pre-assess future claims. Abstract: From 2006 to 2020, UK nutrition and health claims were assessed by the European Food Safety Authority (EFSA) under EU Nutrition and Health Claims Regulations (2006). Since Brexit, UK applications are considered by the UK Nutrition and Health Claims Committee (UKNHCC). EFSA guidance documentation drawing together claims related to appetite ratings, weight management, and blood glucose concentrations was most recently published in 2012. 61 EFSA scientific opinions on appetite-related health claims applications from 2010 to 2020 were reviewed. Fifty-five related to hunger, fullness, energy intake, satiation and satiety were rejected, whereas three weight management claims and three blood glucose levels claims were authorised. 17 novel categories of reasons for claims application rejection were synthesised via Inductive Content Analysis (7 main-, 10 sub-categories). The resultant conceptual framework presented herein aims to support commercial pre-assessment of future appetite-related health claim applications and stimulate discussion regarding appetite-related health claims legislation in the new era of UKNHCC.